G82(P) Exploring the acceptability of a clinical decision rule to identify paediatric burns due to maltreatment. (27th April 2015) - Johnson, EL; Maguire, SA; Hollén, LI; Kemp, AM
Abstract : Objective: A Clinical Decision Rule (CDR) was developed from a systematic review and epidemiological study to identify burns due to child maltreatment. Prior to an implementation evaluation, we wish to explore clinician's response to the CDR, and the likelihood that it would influence their decision making. Methods: A semi-structured questionnaire of 55 Health professionals in 8 Emergency Departments (3 paediatric) and two burns unit's explored demographics, recognition of maltreatment utilising four case vignettes (1: suspect maltreatment, 2: consider maltreatment, 1: likely unintentional), and likelihood of taking action recommend by CDR. Analysis: Fisher's exact test and logistic regression. Results: In an analysis of potential variables, (professional grade, child protection (CP) training or paediatric burns training), the most influential in accurately identifying maltreatment was professional grade (Odds Ratio 2.95, 95% CI 1.39–6.25). Lower grade doctors were most likely to take the action recommended by the CDR, whilst higher grade doctors would do so with a proviso e.g. senior CP colleague advice. More CP training did not correlate to accuracy in identifying suspected or concerning cases, but did correlate with correctly identifying the unintentional case (p = 0.041) and with a proviso to taking CDR recommended action (p = 0.056). Paediatric burns training was not an influential variable. Conclusions: While lower grade doctors are the least accurate at identifying burns due to maltreatment, they are the most likely to follow this CDR. However, those with the least knowledge of CP are least likely to follow the CDR recommended action.